Genetic Diversity and Multiplicity of Plasmodium falciparum Infection in Southeast Asia: New Insights from a Systematic Review - Praswitasari, Rengganis; Husada, Dominicus; Hasan, Nur Aini; Adnyana, I Made Dwi Mertha (Pandawa Institute, 2026)
Plasmodium falciparum caused four million new malaria cases in Southeast Asia in 2023, with heterogeneous transmission patterns and the development of artemisinin resistance. The merozoite surface protein genes (msp-1 and msp-2) serve as genetic markers for analyzing the parasite population structure and multiplicity of infection (MOI). However, a comprehensive synthesis of regional data is limited. This study aimed to determine the genetic diversity and MOI of P. falciparum in Southeast Asia. This systematic review was guided by PRISMA guidelines with searches in the Scopus, PubMed, ProQuest, and Google Scholar databases (2014–2024). The inclusion criterion was observational studies, analyzing the genetic diversity of P. falciparum via msp-1 and msp-2 markers in Southeast Asia. The extracted data included the frequency of msp-1 and msp-2 family alleles, the prevalence of polyclonal infections, and the mean MOI value. Quality assessment was performed via the joanna briggs institute critical appraisal tools with narrative synthesis following the synthesis without meta-analysis (SWiM) guidelines. Fifteen studies; Indonesia (40%), Thailand (26.67%), Myanmar (20%), Vietnam and Malaysia (6.66%) with 1,830 samples successfully genotyped from 2,130 collected samples. The MAD20 (msp-1) allele dominated most locations, with frequencies of up to 100% in Lampung. The distribution of msp-2 alleles showed geographical variation, with FC27 dominating in Papua (96.2%) and 3D7/IC in Vietnam (97.0%). The prevalence of polyclonal infection ranged from 0-84.6%, with MOI values ranging from 1.0-2.93. The hyperendemic areas presented high MOIs (>2.0), whereas the hypoendemic areas presented MOIs close to 1.0, confirming a positive correlation with malaria transmission intensity. The P. falciparum population in Southeast Asia shows high genetic diversity, with geographically variable allele distribution patterns, and MOI values are correlated with malaria endemicity levels. These findings support the need for regional molecular surveillance and a polyvalent approach to the development of msp-based vaccines.